Adaptive management: where are we now? - Rist, Lucy; Campbell, Bruce M.; Frost, Peter (Environmental Conservation, 2013)
Adaptive management (AM) emerged in the literature in the mid-1970s in response both to a realization of the extent of uncertainty involved in management, and a frustration with attempts to use modelling to int egrate knowledge and make predictions. The term has since become incre asingly widely used in scientific articles, policy documents and manag ement plans, but both understanding and application of the concept is mixed. This paper reviews recent literature from conservation and natu ral resource management journals to assess diversity in how the term i s used, highlight ambiguities and consider how the concept might be fu rther assessed. AM is currently being used to describe many different management contexts, scales and locations. Few authors define the term explicitly or describe how it offers a means to improve management ou tcomes in their specific management context. Many do not adhere to the idea as it was originally conceived, despite citing seminal work. Sig nificant confusion exists over the distinction between active and pass ive approaches. Over half of the studies reporting to implement AM cla imed to have done so successfully, yet none quantified specific benefi ts, or costs, in relation to possible alternatives. Similarly those st udies reporting to assess the approach did so only in relation to spec ific models and their parameterizations; none assessed the benefits or costs of AM in the field. AM is regarded by some as an effective and well-established framework to support the management of natural resour ces, yet by others as a concept difficult to realize and fraught with implementation challenges; neither of these observations is wholly acc urate. From a scientific and technical perspective many practical ques tions remain; in particular real-world assessments of the value of exp erimentation within a management framework, as well as of identified c hallenges and pathologies, are needed. Further discussion and systemat ic assessment of the approach is required, together with greater atten tion to its definition and description, enabling the assessment of new approaches to managing uncertainty, and AM itself.
Keywords: Adaptive Management; Decision making; Natural resource management; conservation; experimental management; uncertainty